The Effect of the Level of Monopoly of the Economic Sectors on the International Attractivity and Introduction of Innovations (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines the processes associated with the impact of the degree of monopolization of sectors of the economy on investment attractiveness and the introduction of innovations. The impact of the level of network monopolization on investment attractiveness and innovation has been systematically analyzed. Assessing the current level of monopolization of the industry, the problematic cases of the process of ensuring investment attractiveness were studied. The conditions and opportunities for investment attractiveness and innovation have been systematized by reducing the level of monopolization of the industry. Scientific proposals and practical recommendations on overcoming the existing shortcomings in this regard are given.